2007
DOI: 10.1080/13625180600983108
|View full text |Cite
|
Sign up to set email alerts
|

The role of men in family planning decision-making in rural and urban Nigeria

Abstract: Deciding about contraception should be done jointly by men and women in South West Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 8 publications
4
34
0
7
Order By: Relevance
“…Although Islam does not prohibit the use of contraception, some beliefs still seem to have an effect on the use of contraception (32). In agreement with our findings, Orji et al reported that religion was found to influence the attitude of married Nigerian men towards family planning (33). Another study by Onwuhafua et al reported the reasons for female health extension workers not using any family planning methods; they were the side effects, not being married, not being sexually active, and religious beliefs (34).…”
Section: Discussionsupporting
confidence: 81%
“…Although Islam does not prohibit the use of contraception, some beliefs still seem to have an effect on the use of contraception (32). In agreement with our findings, Orji et al reported that religion was found to influence the attitude of married Nigerian men towards family planning (33). Another study by Onwuhafua et al reported the reasons for female health extension workers not using any family planning methods; they were the side effects, not being married, not being sexually active, and religious beliefs (34).…”
Section: Discussionsupporting
confidence: 81%
“…Less than 2% of women and almost 20% of men were unsure. This disparity in the proportion of women and men who were unsure may indicate how absent men are or feel from reproductive health services [2124]. It may also reflect the fact that most methods of contraception are not used by men, who therefore had to hypothesize about their partner’s intentions.…”
Section: Discussionmentioning
confidence: 99%
“…A study from India indicated that 74% of the subjects felt that the decision regarding the practice of family planning methods and the number of children had to be made by the couple (Rajesh Reddy, Premarajan, Narayan, & Mishra, 2003). A Nigerian study also indicated that most men believed in a decision about family planning being made jointly by the spouses (Orji et al, 2007). Yue, O'Donnell, and Sparks (2010) reported that a greater majority of contraceptive users (94%) have discussed family planning with their spouses than nonusers (55.9%) have (Yue et al, 2010).…”
Section: Discussionmentioning
confidence: 99%